PENGARUH FAKTOR-FAKTOR PSIKOLOGIS KONSUMEN TERHADAP KEPUTUSAN MEMILIKI MOBIL TOYOTA AVANZA DI MALANG TOWN SQUARE (MATOS) - Elisabeth S. Meilinda; Anni Yudiastuti; Cornelius Niwadolo (Akubis : Jurnal Akuntansi dan Bisnis, 2020)
Along with the development of modern era caused so muchcompetition in an increasingly competitive business world.This can be seen with the variations of new products withbrilliant innovation. The result of this competition is thatconsumer can choose a variant product with higher quality,so that in decisions making process consumers can chooseaccording to their ability to buy, taste, and quality of theproduct itself. This study aims to determine the effect ofpsychological variables of consumers to the decision inhaving Toyota Avanza in the Malang Town Square (MATOS).The population of this study is selected using the selectioncriteria of population and obtained 100 respondents whoown Avanza car and parked in MATOS. The research sampleis using 50 respondents. Data analysis method used ismultiple linear regression analysis. Psychological variablesused in this study are motivation, perception, learning, andbeliefs and attitudes. Each variable has certain indicators.Motivation variable consists of three indicators, namely theneeds of prestige, the desire for recognition, and serviceavailability. Perception variables measures with the carcapability indicator, fuel economy, car facilities, and productadvantages. Learning has an indicator variable of personalexperience, the experience of relatives, and the people'sjudgment of the Toyota brand. Beliefs and Attitudes variablehas indicators the compliance with the quality of the car,safety desire, interest and loyalty to the brand models.The results of this study showed that only one variable thathas an influence on purchasing decisions avanza car, whichis learning. Motivation, perceptions, and beliefs and attitudesvariables did not affect the decision in having Toyota Avanzain Malang Town Square (MATOS)